Energy-efficient scalable routing algorithm based on hierarchical agglomerative clustering for Wireless Sensor Networks - Chai, Xuguang; Wu, Yalin; Feng, Lei (Alexandria engineering journal, 2025)
In hierarchical Wireless Sensor Networks (WSNs), the unbalanced energy consumption caused by multi-hop routing poses requirements for the cluster head’s selection and distribution of clusters. Aiming to improve the network lifetime and achieve the balance of energy consumption among sensor nodes, we propose an Energy efficient Scalable Routing algorithm based on Hierarchical Agglomerative Clustering (ESR-HAC) for WSNs by jointly optimizing the cluster formation and energy efficiency of inter-cluster communication. Firstly, to reduce the transmission cost and time/space complexity during the clustering process, a hierarchical clustering method is proposed to achieve a reasonable cluster distribution. Secondly, by taking into account of multiple parameters such as the coverage range, connectivity and remaining energy of sensor nodes, a cost function for cluster head’s selection is defined to reduce the communication overhead between member nodes and cluster heads. Furthermore, to resolve the hot spot problem caused by inter-cluster data forwarding, a genetic algorithm is introduced to obtain the optimal inter cluster routing to balance the network energy consumption. The experimental results show that our algorithm can obtain better energy balance of sensor nodes, ensure the effectiveness of data delivery and extend network lifetime.